Maximum likelihood estimation versus least-squares estimation in semi-continuous hidden Markov modelling - Lehmensiek, Robert (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.